2013
DOI: 10.1089/ten.tea.2011.0532
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Tissue-Engineered Blood Vessel Walls Constructed by Adipose-Derived Stem Cells

Abstract: Adipose-derived stem cells (ASCs) can differentiate into smooth muscle cells and have been engineered into elastic small diameter blood vessel walls in vitro. However, the mechanisms involved in the development of three-dimensional (3D) vascular tissue remain poorly understood. The present study analyzed protein expression profiles of engineered blood vessel walls constructed by human ASCs using methods of two-dimensional gel electrophoresis (2DE) and mass spectrometry (MS). These results were compared to norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The mechanical properties of the bioengineered vessel were examined as previously described 13 . Briefly, the bioengineered vessels and normal human HSV with an inner diameter of 4 mm were sectioned circumferentially.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical properties of the bioengineered vessel were examined as previously described 13 . Briefly, the bioengineered vessels and normal human HSV with an inner diameter of 4 mm were sectioned circumferentially.…”
Section: Methodsmentioning
confidence: 99%
“…Several attempts have been made to utilize mature cells or different types of stem cells for blood vessel engineering. Approaches include human aortic smooth muscle cells (HASMCs) 12 , or human adipose-derived stem cells (hASCs) 13 . or coculture of vascular smooth muscle cells (SMCs) with vascular endothelial cell (ECs) 14 15 , or HASMCs with human umbilical vein endothelial cells (HUVECs) 16 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For vascular tissue engineering, bioreactor technology is still under-explored but bioreactors that provide adequate perfusion and fluid flow has shown to provide an optimal environment for adequate tissue formation [43]. Future work will need to specify the optimal cell source used to create an optimal tissue engineered vascular construct [75]. With the rapid expansion in skin tissue engineering, multiple bioreactors have been utilised for in vitro skin generation.…”
Section: Summary and Future Trendsmentioning
confidence: 99%
“…In this study, ASCs-derived smooth muscle cells were seeded into electrospun polycaprolactone-gelatin scaffolds and maturation was induced in a pulsatile bioreactor followed by seeding with endothelial cells differentiated from ASCs (63). Another study compared the proteomic profiles of normal arterial walls with tissue engineered blood vessels developed by ASCs-derived smooth muscle cells seeded into polyglycolic acid scaffolds and conditioned in a pulsatile bioreactor (62). The study identified 38 differentially expressed proteins between normal vessels and engineered grafts, the majority of which were cytoskeletal and actin-related proteins, indicating altered cytoskeletal integrity in ASCs engineered tissues (62).…”
Section: Cell Sourcementioning
confidence: 99%